A comparative study of TVET systems in China and Pakistan: lessons for Pakistan’s economic development - Bano, Naila (Frontiers in Education, 2026)
This study examines the role of Technical and Vocational education and training (TVET) in fostering financial development, drawing lessons from China’s TVET success to improve Pakistan’s system. Using a qualitative approach, 45 documents published between 2010 and 2024 were systematically analyzed through PRISMA-guided selection and thematic coding with NVivo. The findings reveal that China’s robust TVET system, supported by strong policy integration, enterprise collaboration, and sustained funding, has appreciably contributed to employment generation and poverty reduction. In contrast, Pakistan’s TVET system faces demanding situations which include fragmented guidelines, insufficient funding, and weak industry linkages. The study highlights three critical areas for Pakistan: curriculum reform, improved teacher training, and more potent enterprise partnerships. By adapting China’s Effective practices, Pakistan can address skill gaps, improve youth employability, and advance sustainable development goals.